A practical guide to outcome-focused philanthropy - and Twersky, Fay; Grange, Lori (Hewlett Foundation, 2016)
Outcome-focused philanthropy is the Hewlett Foundation’s approach to how we practice strategic philanthropy. It guides how we do our work, from start to finish. We’ve been practicing strategic philanthropy for more than a decade—focusing on what problem or opportunity we’re trying to address, whether we’re achieving our outcomes and why (or why not), and how…